The Implication Of Social Media Toward College Students’ Online Behavior In Bandung - Indri Utami Sumaryanti; Jannah Yuniar (MediaTor (Jurnal Komunikasi), 2022)
In Indonesia, there has been an increasing amount of internet usage. Computer Mediated Communication (CMC) is a form of communication held between two people or more and a computer as the media. While 92,1 % of internet users in Indonesia are college students, it is important to investigate the impact of social media toward their behavior since internet can bring both positive and negative impacts. In this research, 483 college students in Bandung were asked about their Social Network Sites behavior through a structured interview. The data analysis used was MaxQDA software in order to gain the themes. The result of this study discovered that 47% of the participants used social media for more than 6 hours a day. Their top purposes of using social media were communication, entertainment, and information searching. While high social media use is related to social media addiction and several behaviors that might lead to mental health issues, it is possible that this escalation resulted from the Covid-19 pandemic.